The contribution of dance to daily physical activity among adolescent girls - Hooker Steven P; Pate Russell R; O'Neill Jennifer R (BMC, 2011)
Abstract Background Structured physical activity (PA) programs are well positioned to promote PA among youth, however, little is known about these programs, particularly dance classes. The aims of this study were to: 1) describe PA levels of girls enrolled in dance classes, 2) determine the contribution of dance classes to total moderate-to-vigorous physical activity (MVPA), and 3) compare PA between days with a dance class (program days) and days without a dance class (non-program days). Methods Participants were 149 girls (11-18 years) enrolled in dance classes in 11 dance studios. Overall PA was assessed with accelerometry for 8 consecutive days, and girls reported when they attended dance classes during those days. The percent contribution of dance classes to total MVPA was calculated, and data were reduced to compare PA on program days to non-program days. Data were analyzed using mixed models, adjusting for total monitoring time. Results Girls engaged in 25.0 ± 0.9 minutes/day of MVPA. Dance classes contributed 28.7% (95% CI: 25.9%-31.6%) to girls' total MVPA. Girls accumulated more MVPA on program (28.7 ± 1.4 minutes/day) than non-program days (16.4 ± 1.5 minutes/day) (p < 0.001). Girls had less sedentary behavior on program (554.0 ± 8.1 minutes/day) than non-program days (600.2 ± 8.7 minutes/day) (p < 0.001). Conclusions Dance classes contributed a substantial proportion (29%) to girls' total MVPA, and girls accumulated 70% more MVPA and 8% less sedentary behavior on program days than on non-program days. Dance classes can make an important contribution to girls' total physical activity.